1998
DOI: 10.1007/bf02253473
|View full text |Cite
|
Sign up to set email alerts
|

Disulfiram augments oxidative stress in rat brain following bilateral carotid artery occlusion

Abstract: We examined the brain oxidative stress which accompanies 30 min of bilateral carotid artery ligation (BCAL) in terms of changes in brain levels of glutathione; reduced (GSH) and oxidized (GSSG) forms and the exacerbation of oxidative stress by disulfiram (DSF). These results indicate that BCAL alone decreases GSH content and limits glutathione reductase (GR) activity, and these changes were enhanced by DSF pretreatment. Similar observations were recorded with DSF alone. GR activity (74.3 +/- 4.0 micromol min(-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Several studies have suggested that oxidative stress plays a role in ischaemia‐related brain damage 15 , 16 . Further observations regarding the occurrence of ischaemic stroke in SHRSP are of great interest because increased oxidative stress may directly affect brain damage in SHRSP.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have suggested that oxidative stress plays a role in ischaemia‐related brain damage 15 , 16 . Further observations regarding the occurrence of ischaemic stroke in SHRSP are of great interest because increased oxidative stress may directly affect brain damage in SHRSP.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the studies report that dithiocarbamates per se have similar effects. Disulfiram was found to rapidly decrease GSH levels in vitro [53], and disulfiram administration in rat brains caused GSH decline with a concomitant increase in GSSH levels [54,55], formation of disulfiram-glutathione conjugates [56] and inhibition of GR activity [54,55]. PyDTC has shown an analogous impact on GSH content in vivo [57].…”
Section: Biological Effects Of a Mixture Of Diethyldithiocarbamate Anmentioning
confidence: 91%